Bend the knee or seize the throne : leadership lessons from The Seven Kingdoms - Tong, Nathan; Urick, Michael J. (Exploring effective leadership practices through popular culture, 2023)
Exploring the extensive world of HBO's Game of Thrones series to illustrate leadership theories supported by scholarly research, Bend the Knee or Seize the Throne analyzes characters and scenarios from the series to demonstrate and deconstruct different examples of leadership and leader behavior. The expansive fantasy world created by George R. R. Martin provides the perfect backdrop for diverse discussions around various types of leadership, from authoritarian and servant to transactional and charismatic, and different forms of power and influence. How is power used and abused? What are the effects of abuse of power? An examination of ethics and motivation, along with concepts of justice and cultural awareness, feed into a comprehensive dive into manifestations of leadership throughout the Seven Kingdoms. Informing readers from students and aspiring leaders through to experienced leaders, managers, consultants, and educators, this fun and accessible exploration of leadership theories appeals to both practitioners and fans of Game of Thrones. Nathan Tong and Michael J. Urick bridge the gap between academic theories of leadership and familiar characters and situations from a pop-culture phenomenon.